Dietary Micronutrients from Zygote to Senility: Updated Review of Minerals’ Role and Orchestration in Human Nutrition throughout Life Cycle with Sex Differences - Mohamed A. Farag (MDPI AG, 2021)
Micronutrients such as selenium, fluoride, zinc, iron, and manganese are minerals that are crucial for many body homeostatic processes supplied at low levels. The importance of these micronutrients starts early in the human life cycle and continues across its different stages. Several studies have emphasized the critical role of a well-balanced micronutrient intake. However, the majority of studies looked into or examined such issues in relation to a specific element or life stage, with the majority merely reporting the effect of either excess or deficiency. Herein, in this review, we will look in depth at the orchestration of the main element requirements across the human life cycle beginning from fertility and pregnancy, passing through infancy, childhood, adolescence, and reaching adulthood and senility, with insight on the interactions among them and underlying action mechanisms. Emphasis is given towards approaches to the role of the different minerals in the life cycle, associated symptoms for under- or overdoses, and typical management for each element, with future perspectives. The effect of sex is also discussed for each micronutrient for each life stage as literature suffice to highlight the different daily requirements and or effects.